Improving The Student's Classroom Student's Reasoning Ability In Mathematics Lesson Through Problem Solving Efforts At Sdn 13 Kubang - Zulfetriani Zulfetriani (Fakultas Sastra Universitas Ekasakti, 2017)
Basic education aims to provide basic skills to learners to develop their lives as individuals, community members, citizens and members of the human race and prepare learners to follow the next education. Primary education is organized to develop skills attitudes and provide the basic knowledge and skills necessary to live in communities and prepare learners who are eligible for secondary education (UU Sisdiknas No. 20 Year 2003 article 13). In teaching and learning activities, a teacher would have hope of desire for learners can get the maximum value possible, in accordance with the learning objectives created or desired but what can be in word, reality. For special mathematics subjects, field findings such as EBTANAS, summative test results and daily test scores and report scores indicate that the learners' learning outcomes are still below the numbers that may be unsatisfactory in both low and class high. From some study results and opinions of experts, the low mathematics learning outcomes of students is not because they are not able to perform calculations, but because they do not understand the problems contained in the problem. Hudoyo (in Laily Hasbullah: 2000: 1) states that questions related to numbers are not so difficult for learners, but the problems that use sentences are very difficult for learners who have less or less ability.